Land Use Change and Forest Fragmentation Analysis: A Geoinformatics Approach on Chunati Wildlife Sanctuary, Bangladesh - Md Farhadur Rahman; Mohammed Jashimuddin; Kamrul Islam; Tapan Kumar Nath (Journal of Civil Engineering and Environmental Sciences - Peertechz Publications, 2016)
Geoinformatics approach is increasingly used to monitor land use change as well as forest fragmentation due to availability of Landsat satellite data. In Bangladesh many initiatives have been taken to prepare land use maps but forest fragmentation modelling is quite new. In this research, geoinformatics approach is thoroughly used to determine land use changes of Chunati Wildlife Sanctuary from 2005 to 2015. Three time frame data sets i.e. 2005, 2010 and 2015 were used for assessing forest fragmentation. Forest intactness is measured by the proportion of four spatial patterns i.e. core, perforated, edge and patches. Previously tree cover and density was considered as the yardstick to measure forest health and ecosystem but recent studies regarding forest fragmentation have uncovered many harmful impacts of it. However, in this research authors observed 26.44% decrease in forest cover, 37.56% decrease in water bodies and 56.05% increase in cropland, 42.52% increase in barren lands, 69.01% increase in afforested area in between 2005 and 2010. Overall condition was leading to substantial forest fragmentation. Due to initiation of restoration activities positive results have come out which are 18.86% and 38.01% decrease in cropland and barren land respectively accompanied by 58.92% increase in forest between 2010 and 2015. As forest fragmentation is highly correlated with conversion of forest into non forest uses, core areas and perforated areas significantly reduced to 503 hectares and 1212 hectares respectively in between 2005 and 2010, associated with a slight increase of 343 hectare edged area forest whereas overall forest cover reduced signifi cantly. Later, positive changes result 503 hectare increase in core areas along with 762 hectares decrease in patched forest from 2010 to 2015 which is surely a good sign.